MODEL PENGUKURAN KESIAPAN IMPLEMENTASI ARSITEKTUR ENTERPRISE BERBASIS CRITICAL SUCCESS FACTOR - Adam Sekti Aji; Teduh Dirgahayu; Hanson Prihantoro Putro (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
This paper discusses about Enterprise Architecture (EA) implementation readiness measurement model. The definition of EA is a framework or blueprint that used by organization to achieve business objectives by identifying key strategies of business, information, applications, and technology and its impact on business functions. Measuring the readiness of EA implementation on an institution is useful to reduce potential losses due to EA implementation failures. By identifying the factors supporting the successful implementation of EA, an EA implementation readiness measurement model can be formulated and can be used as a reference to know the readiness of an institution in the implementation of EA.